Conquer Tonsillitis Without Surgery – General And Homoeopathic Measures (Homoeopathy for All, 2025)
Tonsillitis is common, especially in  children. Tonsillitis is inflammation  of the tonsils most commonly caused  by viral or bacterial infection. The  most common problems affecting  the tonsils are recurrent infections  (throat or ear) and significant  enlargement or obstruction that  causes breathing and swallowing  problems. The condition can occur  occasionally or recur frequently.  This article provides an overview  of the aetiology, diagnosis, and  appropriate general & homoeopathic  management of this disorder.
Keywords: inflammation; appropriate general; soft glandular tissue; Aetiology